Thrombosis Prevention by Coagulation and Platelet Aggregation Inhibitors, in Hyperlipemic Rats - Renaud, S; Lecompte, F (Thrombosis and Haemostasis, 1970)
Phenylbutazone, oxyphenbutazone, and sulfinpyrazone were equally effective at the dosage of 100 mg/kg (per os) in inhibiting thrombin- and ADP-induced platelet aggregation in hyperlipemic rats, and in preventing the development of thrombosis initiated by the intravenous injection of an endotoxin. Despite a slight anticoagulant effect of these substances, their antithrombotic activity appears to be due mostly to inhibition of platelet aggregation.Thrombosis in hyperlipemic rats could also be prevented by a dicoumarol derivative, acenocoumarin, which only inhibits coagulation. Therefore, both platelet aggregation and fibrin formation appear to be essential for the occurrence of large thrombi under these conditions. Nevertheless, although acenocoumarin has no direct effect on platelet aggregation, it could indirectly affect this phenomenon by blocking the formation of thrombin, which is suspected of being the agent responsible for initiating thrombosis in hyperlipemic rats.Low doses of phenylbutazone and acenocoumarin, in condition, which when given alone were ineffective in inhibiting thrombosis, could decrease the severity of thrombosis by 33%. The substance GP45840, when added in vitro to platelet-rich plasma as well as given per os to hyperlipemic rats, was no more effective than sulfinpyrazone in inhibiting platelet aggregation. Nevertheless, this substance was significantly more efficient in reducing thrombosis than was sulfinpyrazone, apparently through some additional anticoagulant activity. The results of these experiments suggest that it could be beneficial to affect both coagulation and platelet aggregation in order to satisfactorily prevent thrombosis.